INVESTIGATION OF THE RELATIONSHIP BETWEEN HEPATITIS C AND LIVER CANCER DATABASES - Gözde Öztan; Halim İşsever (Sabiad)
Objective: The global prevalence of hepatitis C virus (HCV) infections has recently reached epidemic levels. Liver cancer, known as hepatocellular carcinoma (HCC), is extremely lethal once detected and is common in those with persistent HCV infection without access to appropriate therapy. Recent studies have shown that HCV-encoded proteins contribute to cancer development in infected hepatocytes. To develop treatments for HCC and liver cancer, it is essential to understand how viral proteins interact with host cell proteins. Material and Methods: We used the Reactive, WikiPathways, KEGG, and Biocarta databases to identify common DEG pathways associated with HCC and HCV. Results: Through bioinformatics approaches, this study identified common differential genes and related pathways to determine the molecular mechanisms underlying the pathogenesis of hepatitis C-related liver cancer. Investigating gene-gene interactions may lead to more effective treatment approaches. The liver cancer transcriptome identified 708 genes associated with HCC. Data on hepatitis C infection revealed 1768 genes linked to HCV. The Venn diagram then identified 152 DEGs common to HCV and HCC. Conclusion: We believe that hepatitis C-related liver cancer can be predicted using the first 20 target genes identified through PPI analysis.